Teaching social science research methods to undergraduate medical students: The state of the art and opportunities for practice and curriculum development. Issue 3 (October 2017) - Forrest, Simon
There is an expectation that medical students in the UK will be able to demonstrate conversancy with social science relevant to medicine and health, including the means by which the relevant bodies of knowledge are generated through the use of social science research methods. This paper explores the structural and pedagogical challenges and opportunities posed by this demand. To achieve this a small scale research project seeking to establish the 'state of the art' with respect to teaching and learning about these research methods was implemented. It was found that there is little formal reporting of practice in the literature and that this is a field largely unsupported with materials and resources. However, there were some common features in the ways that practitioners approach, organise and deliver the provision; and it was found that almost all the provision takes place in the early part of medical education. It is suggested that continuing problems with the status of social sciences, lack of clarity about whether the purpose is to enrich medicine with knowledge about health and generated by the social sciences, and/or explore the ontological and epistemological tensions between natural and social sciences coupled with the status of social scientists in medical education, may limit capacity to develop the field.